Recent Advances for Electrode Modifications in Flow Batteries: Properties, Mechanisms, and Outlooks. Issue 5 (30th January 2023) - Wu, Min; Fang, Maolin; Nan, Mingjun; Chen, Xiangnan; Ma, Xiangkun
Abstract: Flow batteries (FBs) have been demonstrated in several large‐scale energy storage projects, and are considered to be the preferred technique for large‐scale long‐term energy storage in terms of their high safety, environmental friendliness, and long life, including all‐vanadium flow batteries (VFBs) and Fe‐Cr flow batteries (ICFBs). As the electrochemical reaction site, the electrode parameters, such as the specific surface area, active site, and so on, have a significant impact on the flow battery performance and reliability. Extensive research has been carried out on electrode modification to improve the current density and energy efficiency of the FBs. In this review, the reaction mechanisms of VFBs and ICFBs are discussed in detail firstly, and then the electrodes modification methods are overviewed and summarized from four aspects: self‐modification, carbon‐based electrocatalysts, metal‐based electrocatalysts and composite electrocatalysts. Finally, the recent catalytic mechanism, in situ characterization technology, and future research directions are presented. Abstract : As the electrochemical reaction site, the electrode parameters, such as the specific surface area, active site, and so on, have a significant impact on the flow battery performance and reliability. In this review, the reaction mechanisms of VFBs and ICFBs are discussed in detail firstly, and then the electrode modification methods are overviewed and summarized from four aspects: self‐modification, carbon‐based electrocatalysts, metal‐based electrocatalysts and composite electrocatalysts.